Seronegative hepatitis C virus infection in Polish blood donors—Virological characteristics of index donations and follow‐up observations. Issue 3 (21st November 2019) - Grabarczyk, Piotr; Kubicka‐Russel, Dorota; Kopacz, Aneta; Liszewski, Grzegorz; Sulkowska, Ewa; Zwolińska, Paulina; Madaliński, Kazimierz; Marek, Maciej; Szabelewska, Małgorzata; Świątek, Ewa; Laskus, Tomasz; Radkowski, Marek
Abstract : Abstract: Nucleic acid testing (NAT) was implemented in Poland in 1999 for screening of plasma for fractionation and for all blood donors in 2002. To analyze seronegative NAT‐positive samples representing hepatitis C virus (HCV) window‐period (WP) in the years 2000 to 2016 and to determine infection outcome. We analyzed results of 17 502 739 donations screened in minipools (6‐48) or individually. Index samples underwent viral load (VL) quantification, genotyping and Ag, and anti‐HCV re‐testing using chemiluminescence (CMIA), electrochemiluminescence (ECLIA), and fourth‐generation enzyme‐linked immunosorbent assay (IV EIA) assays. HCV‐seronegative infections were identified in 126 donations (7.2/mln donations; 95% confidential intervals, 6.0‐8.6). Frequency of NAT yields was decreasing over time. Of the initial 126 seronegative index cases 106 were retested: 32.1% were reactive in IV EIA, 11.3% in ECLIA, and 1.9% in CMIA. The lowest VL correlated with absent anti‐HCV and HCV Ag, while VL was highest when the antigen was detectable and then it decreased when anti‐HCV appeared at a level detectable by sensitive third generation tests while retesting. The proportion of genotype 1 was 38.9% in samples positive only for HCV RNA and 71.4% in samples that were anti‐HCV reactive in re‐testing. In parallel, genotype 3 frequency was 50% in the former group and 21% in the latter. NAT is an effective measure to limit HCV transmission by transfusion and IV EIA seems to have higher clinical sensitivity than ECLIA. Samples representing likely successive phases of early HCV infection were characterized by different genotype distribution probably due to very early elimination of genotype 3. Highlight: NAT is highly effective in prevention of transmission of HCV seronegative infections. In nearly 7% of followed up donors antibodies appeared later than 50 days after index donation. The highest clinical sensitivity was demonstrated by the IVth generation tests. Among the third generation assays, ECLIA showed higher sensitivity than CMIA. Samples representing likely successive phases of early HCV infection demonstrated different genotype distribution.